Pengembangan Model Latihan Forehand Drive Tenis Lapangan Berbasis Situasi Bermain - Jatra, Rices; Yulianti, Mimi; Kurniawan, Wahyu; Alnedral, Alnedral; Firdaus, Kamal (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2024)
Riau Tennis Camp's tennis performance is currently experiencing a decline, this can be seen by the absence of Riau Tennis Camp players winning the National Junior Tennis Championship in Singles. To achieve maximum performance, you need maximum practice, especially in mastering basic tennis techniques. The most dominant basic technique in tennis is the forehand groundstroke. So this research aims to improve basic tennis technical skills, especially Forehand Drive Tennis. This research is an R and D development research on the development of a field tennis Forehand Drive training model based on playing situations using the Borg and Gall development model which includes 10 R&D research stages as follows: (1)Research and information collecting (research and data collection), (2)Planning (planning), (3) (initial product draft development), (4) Expert validation, (5) Revision of expert validation results, (6) (main field trial), (7) (revisions to products), (8) (conducting operational field trials), (9) (final product revision), (10) (dissemination and implementation)